1999
DOI: 10.1103/physrevb.60.1592
|View full text |Cite
|
Sign up to set email alerts
|

Holes in thetJzmodel: A diagrammatic study

Abstract: The t-J z model is the strongly anisotropic limit of the t-J model which captures some general properties of doped antiferromagnets ͑AF's͒. The absence of spin fluctuations simplifies the analytical treatment of hole motion in an AF background, and allows us to calculate single-and two-hole spectra with a high accuracy using a regular diagram technique combined with a real-space approach. At the same time, numerical studies of this model via exact diagonalization on small clusters show negligible finite-size e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
87
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(96 citation statements)
references
References 41 publications
9
87
0
Order By: Relevance
“…Note that this trend is consistent with the prediction from the spin polaron picture. 9,10,18 While at JϾ0.3t the p (,) and p (,0) states are clearly excited states, the energy levels look quite complicated in the range 0.2tрJр0.3t. Note that the d, p (,) and p (,0) states are almost degenerate at Jϭ0.3t, although the d state is still the ground state.…”
Section: Low-lying States With Different Symmetriesmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that this trend is consistent with the prediction from the spin polaron picture. 9,10,18 While at JϾ0.3t the p (,) and p (,0) states are clearly excited states, the energy levels look quite complicated in the range 0.2tрJр0.3t. Note that the d, p (,) and p (,0) states are almost degenerate at Jϭ0.3t, although the d state is still the ground state.…”
Section: Low-lying States With Different Symmetriesmentioning
confidence: 99%
“…Furthermore, it has been shown that such terms favor the p-wave state. 10 This shows that the physics of the low-lying p state may not be irrelevant. Therefore it is important to understand the similarities and differences between the properties of the d x 2 Ϫy 2 and the p states.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…= 0, the t ′ − J z − J ⊥ model hole pair symmetry on a plaquette is d-wave for t ′ > 0 and s-wave for t ′ < 0, as in the general t ′ − J z model strong coupling case. As mentioned previously, some approaches have suggested p-wave hole-pair symmetry for some range of generally intermediate or small J/t or J z /t 20,31,32,33 . However, other t − J numerical results 22,34,35,37 indicate that d-wave features of the strong-coupling limit may persist down to physically relevant intermediate coupling (J/t ≈ 0.3 − 0.5).…”
Section: T − Jz Modelmentioning
confidence: 99%
“…4,5 One can argue that the t-J z model should reproduce qualitatively the holes' ground state of the isotropic t-J model, although the details of such states might differ. Moreover, for the bulk stripe phase in this model a very close quantitative agreement between the analytical and numerical methods have been demonstrated in our previous work.…”
mentioning
confidence: 99%